A Few Bad Apples or the Logic of Capitalism?: Neoliberal Globalization in the Economic Crime Drama Since the Millennial Turn. Issue 4 (1st December 2021) - von Dirke, Sabine
Abstract: This article investigates how neoliberal globalization has been mediated through audiovisual narratives since the 2000s. It identifies a cluster of films, produced by and circulating on German public television, which use the generic conventions of the popular crime genre to constitute a sub-genre—the televisual economic crime drama. Using a content and textual analysis that focuses on the backdrop of historical context and genre norms, the article examines key tropes to assess the critical potential of this sub-genre. The analysis demonstrates that both the containment theme of "a few bad apples" and a systemic critique can structure these narratives of neoliberalism. At its best, the televisual economic crime drama argues that alternatives to neoliberalism are possible by referencing Germany's history of the social market economy and by featuring characters as well as images of active citizenship, solidarity, and collective action in the workplace.